Alterations of polyunsaturated fatty acid metabolism in ovarian tissues of polycystic ovary syndrome rats. Issue 7 (30th March 2018) - Huang, Rong; Xue, Xinli; Li, Shengxian; Wang, Yuying; Sun, Yun; Liu, Wei; Yin, Huiyong; Tao, Tao
Abstract: The metabolism of polyunsaturated fatty acids (PUFAs) remains poorly characterized in ovarian tissues of patients with polycystic ovary syndrome (PCOS). This study aimed to explore alterations in the levels of PUFAs and their metabolites in serum and ovarian tissues in a PCOS rat model treated with a high‐fat diet and andronate. Levels of PUFAs and their metabolites were measured using gas/liquid chromatography‐mass spectrometry after the establishment of a PCOS rat model. Only 3 kinds of PUFAs [linoleic acid, arachidonic acid (AA) and docosahexaenoic acid] were detected in both the circulation and ovarian tissues of the rats, and their concentrations were lower in ovarian tissues than in serum. Moreover, significant differences in the ovarian levels of AA were observed between control, high‐fat diet‐fed and PCOS rats. The levels of prostaglandins, AA metabolites via the cyclooxygenase (COX) pathway, in ovarian tissues of the PCOS group were significantly increased compared to those in the controls. Further studies on the mechanism underlying this phenomenon showed a correlation between decreased expression of phosphorylated cytosolic phospholipase A2 (p‐cPLA2) and increased mRNA and protein expression of COX2, potentially leading to a deeper understanding of altered AA and prostaglandin levels in ovarian tissues of PCOS rats.